Counseling with Cognitive Behavioral Therapy Approach to Manage Student Academic Stress - Mulyati, Sri (Proceedings of Siliwangi Annual International Conference on Guidance and Counselling, 2023)
The importance ofAdolescence is a turbulent time marked by conflict and mood swings. The inability of individuals to manage pressure in life can be a source of stress. One of the causes of stress sometimes comes from the school environment which should be a place that is quite comfortable and healthy for the physical and psychological development of students. Academic stress is a phenomenon that is widespread in various stages of the education system, will have a negative impact on the personal, emotional and physical well-being of students and their learning. research to be conducted by the author.